(untitled) (Research, Society and Development, 2024)
The purpose of the current scientific paper is to present a study about the assessment of the influence of self-evaluated stress during the manifestation of the following dermatologically diagnosed diseases: acne vulgaris, atopic dermatitis and seborrheic dermatitis. The epistemological data was collected through two moments: first, the filling of the "Perceived Stress Scale (PSS-10)" form, and later, the filling of the “Dermatology Life Quality Index - DLQI – BRA’’ form through the online tool “Google Forms”. The data acquired from the forms was transcribed to spreadsheets and later processed by the GraphPad Prism 9 version 9.5.1 Software (528), which allowed the analysis of the correlation between studied variables and the elaboration of the Dispersion Diagram. In total, 54 questionnaires were sent; 40 answered by women and 14 by men. Atopic dermatitis as an isolated dermatologic diagnosis was reported by 10 individuals, acne vulgaris by 21 individuals, and seborrheic dermatitis by 9. Through the statistical analysis of the collected data, the conclusion reached is that there’s no significant relation between the “Self-evaluated stress” and “Skin condition” variables contemplated by the study.